EVALUATION OF THE SUSTAINABILITY OF THE TURKISH WEALTH FUND WITHIN THE FRAMEWORK OF UN SDGS (Third Sector Social Economic Review, 2024)
The study aims to evaluate the sustainability of the Turkish Wealth Fund (TWF) by examining the information regarding the United Nations (UN) Sustainable Development Goals (SDGs) included in the sustainability, integrated and annual reports disclosed by TWF companies between 2017-2021. Within the scope of the research,5-year data of a total of 22 companies which are 4 in the Energy sector, 6 in the Financial Services sector, 3 in the Mining and Iron and Steel sector, 3 in the Agriculture and Food sector, 3 in the Technology and Telecom sector and 3 in the Transportation and Logistics sector were examined using descriptive content and frequency analysis methods. In this context, according to the results obtained from 95 reports examined for a total of five years, it was determined that the companies included SDGs in their annual reports the most, with 37.5%. The sectors that include SDGs the most in the reports are “Technology and Telecom” and “Financial Services”. The most frequently disclosed SDG indicators were found to be “SDG 5 Gender Equality” and “SDG 9 Industry, Innovation and Infrastructure”. “SDG 14 Life Above Water” and “SDG 6 Clean Water and Sanitation” are the least disclosed indicators.
Keywords: Sustainable Development Goals (SDGs); Non Financial Reporting; Turkish Wealth Funds